A missense variant in SHARPIN mediates Alzheimer’s disease-specific brain damages - Park, Jun Young; Lee, Dongsoo; Lee, Jang Jae; Gim, Jungsoo; Gunasekaran, Tamil Iniyan; Choi, Kyu Yeong; Kang, Sarang; Do, Ah Ra; Jo, Jinyeon; Park, Juhong; Park, Kyungtaek; Li, Donghe; et al. (Translational Psychiatry, 2021)
Established genetic risk factors for Alzheimer’s disease (AD) account for only a portion of AD heritability. The aim of this study was to identify novel associations between genetic variants and AD-specific brain atrophy. We conducted genome-wide association studies for brain magnetic resonance imaging measures of hippocampal volume and entorhinal cortical thickness in 2643 Koreans meeting the clinical criteria for AD (n = 209), mild cognitive impairment (n = 1449) or normal cognition (n = 985). A missense variant, rs77359862 (R274W), in the SHANK-associated RH Domain Interactor (SHARPIN) gene was associated with entorhinal cortical thickness (p = 5.0 × 10−9) and hippocampal volume (p = 5.1 × 10−12). It revealed an increased risk of developing AD in the mediation analyses. This variant was also associated with amyloid-β accumulation (p = 0.03) and measures of memory (p = 1.0 × 10−4) and executive function (p = 0.04). We also found significant association of other SHARPIN variants with hippocampal volume in the Alzheimer’s Disease Neuroimaging Initiative (rs3417062, p = 4.1 × 10−6) and AddNeuroMed (rs138412600, p = 5.9 × 10−5) cohorts. Further, molecular dynamics simulations and co-immunoprecipitation indicated that the variant significantly reduced the binding of linear ubiquitination assembly complex proteins, SHPARIN and HOIL-1 Interacting Protein (HOIP), altering the downstream NF-κB signaling pathway. These findings suggest that SHARPIN plays an important role in the pathogenesis of AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Brain; Cognitive Dysfunction; Genome-Wide Association Study; Humans; Magnetic Resonance Imaging; Nerve Tissue Proteins; Ubiquitins